STRATEGI ORANG TUA DALAM MENANAMKAN NILAI-NILAI RELIGIUS PADA ANAK SEBAGAI UPAYA MENCEGAH KENAKALAN REMAJA DI DESA TANJUNGREJO - Wahyudi, Fitri Kurnia; Maulid Agustin (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2024)
The objective of this research is to explore the strategies employed by parents in Tanjungrejo Village to instill religious values in their children, aiming to prevent adolescent delinquency. Religious values are considered crucial for providing moral guidance to adolescents. Using a qualitative approach with a descriptive design, the study utilizes observation, interviews, and documentation for data collection. Data analysis involves reducing, presenting, and drawing conclusions from the gathered information. Findings indicate that parents utilize various tactics, such as setting personal examples, encouraging participation in religious activities like Quranic studies, and maintaining open communication with their children. Religious values serve as a strong moral foundation capable of influencing adolescent decision-making. Nevertheless, parents encounter challenges, particularly concerning their children's reliance on technology. Managing children's exposure to inappropriate content and ensuring the primacy of religious values in education pose significant hurdles for parents. Despite these challenges, parental involvement in instilling religious values is deemed essential in preventing adolescent delinquency. However, addressing influences like technology requires a careful approach to educating children in the digital age. Parents' recognition of their role in their children's education and collaborative efforts to foster an environment supportive of religious values could be crucial in preventing adolescent delinquency in Tanjungrejo Village.